Impact of Severe Extracranial ICA Stenosis on MRI Perfusion and Diffusion Parameters in Acute Ischemic Stroke - Kaesemann, Philipp; Thomalla, Götz; Cheng, Bastian; Treszl, Andras; Fiehler, Jens; Forkert, Nils Daniel (Frontiers in Neurology, 2014)
Purpose: The aim of this study was to investigate the impact of a coexisting internal carotid artery (ICA) stenosis on lesion volumes as well as diffusion and perfusion parameters in acute ischemic stroke resulting from middle cerebral artery (MCA) occlusion. Material and Methods: MRI data of 32 patients with MCA occlusion with or without additional ICA stenosis imaged within 4.5 hours of symptom onset were analyzed. Both groups consisted of 16 patients. Acute diffusion lesions were semi-automatically segmented in apparent diffusion coefficient (ADC) MRI datasets. Perfusion maps of cerebral blood volume (CBV), cerebral blood flow (CBF), mean transit time (MTT) and Tmax were calculated using perfusion-weighted MRI datasets. Tissue-at-risk (TAR) volumes were generated by subtracting the ADC lesion from the hypoperfusion lesion defined by Tmax >6s. Median ADC and perfusion parameter values were extracted separately for the diffusion lesion and tissue-at-risk and used for statistical analysis. Results: No significant differences were found between the groups regarding the diffusion lesion and tissue-at-risk volumes. Statistical analysis of diffusion and perfusion parameters revealed CBV as the only parameter with a significant difference (p=0.009) contributing a small effect (ɛ²=0.11) to the group comparison with higher CBV values for the patient group with a coexisting ICA stenosis, while no significant effects were found for the other diffusion and perfusion parameters analyzed. Conclusion: The results of this study suggest that a coexisting ICA stenosis does not have a strong effect on tissue status or perfusion parameters in acute stroke patients except for a moderate elevation of CBV. This may reflect improved collateral circulation or ischemic preconditioning in patients with a pre-existing proximal stenosis balancing impaired perfusion from the stenosis.